2020
DOI: 10.1590/2177-6709.25.4.068-074.oar
|View full text |Cite
|
Sign up to set email alerts
|

The ability of orthodontists and maxillofacial surgeons in predicting spontaneous eruption of mandibular third molar using panoramic serial radiographs

Abstract: Objective: To evaluate the skill of orthodontists and oral/maxillofacial surgeons (OMFS) in providing a prognosis of mandibular third molars spontaneously erupted, through follow-up panoramic analysis. Methods: 22 orthodontic patients treated without extraction, presenting spontaneously erupted mandibular third molars (n = 44) were analyzed through panoramic serial radiographs. The first panoramic radiograph was obtained just after orthodontic treatment (PR1), in patients aging from 13 to 19 years. A second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…who found that impaction of the third molar is one of the factors more important that influences to a possible extraction of a lower third molar ( 2 , 5 , 8 ). The published literature indicates that a complex location of the third molar would affect the decision due to a positive correlation between the decision to extract a third molar and the probability of producing collateral damage ( 21 ), added to the fact that the professional’s ability to predict a risk or spontaneous eruption in cases of impaction has limitations ( 3 , 4 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…who found that impaction of the third molar is one of the factors more important that influences to a possible extraction of a lower third molar ( 2 , 5 , 8 ). The published literature indicates that a complex location of the third molar would affect the decision due to a positive correlation between the decision to extract a third molar and the probability of producing collateral damage ( 21 ), added to the fact that the professional’s ability to predict a risk or spontaneous eruption in cases of impaction has limitations ( 3 , 4 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The third molar is a tooth characterized by certain variability in its presence or absence, in time of its conformation and calcification, its coronal and root morphology, as well as its eruption course and final position ( 1 ). Added to the above, in approximately 73% of people the lower third molar erupts in the third decade of life with an impaction rate that varies between 9.5% and 39% ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…They noted that severe impactions were associated with postoperative pain, trismus, and swelling with a need for pain medication. However, when the ability to identify the risk of third molar non‐eruption using panoramic radiographic analysis was evaluated, Libdy et al 8 found that both orthodontists and oral maxillofacial surgeons were unable to predict which third molars would become impacted; both groups of specialists indicated extractions in approx. 50% of cases, being unable to distinguish those in which the third molars would erupt normally.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring should be performed every 2 years up to at least the age of 18. The serial analysis of panoramic radiographs, a method widely used for clinical monitoring of orthodontic patients, might be able to increase the accuracy of this prediction [12].…”
Section: Introductionmentioning
confidence: 99%
“…Whenever indicating extraction of third molars, dentists, should have a justifiable reason, taking into account future treatment planning from an orthodontic, surgical, periodontal, and/or prosthetic point of view [12].…”
Section: Introductionmentioning
confidence: 99%